Transformation of Cultural Capital at Borobudur Temple and the Habitus of the Buddhist Society of Krecek Hamlet (Analysis of Pierre Bourdieu's Theory) - Yatno, Tri; Mujiyanto, Mujiyanto; Sudarto, Sudarto; Ngadat, Ngadat (Universitas Muhammadiyah Ponorogo, 2026)
Krecek Hamlet is a Buddhist tourism village that plays an important role in promoting and preserving the noble values of Borobudur Temple. This research aims to analyze the transformation of the cultural capital of Borobudur Temple and the habitus of the people of Krecek Hamlet through the analysis of Pierre Bourdieu's theory. The method used in this research is a case study. The research results stated that Borobudur Temple as a representation of Buddhist teachings is a cultural capital. Borobudur cultural capital has a role in shaping the character and cultural identity of the people of Krecek Hamlet. The habits formed include religious habitus, togetherness, friendliness and tolerance, simplicity, respect for tradition, respect for nature, as well as traditional and spiritual leadership. The habitus of the people of Krecek Hamlet is the result of social interaction. The people of Krecek Hamlet live based on socio-cultural structures and adhere to religious values and traditional norms. The transformation of Borobudur's symbolic capital into the habitus of the people of Krecek Hamlet is performed through the process of reproducing religious culture and local wisdom. This research has many shortcomings, thus it needs to be studied more deeply, especially regarding social media and the digitization of the culture of Buddhists in Krecek Hamlet in preserving religious values and promoting Buddhist tourism.